Is “Just-Get-Started” an effective self-management tactic to improve flossing? - Touznik, Jessica (My University, 2022)
Healthy behaviours are often maintained by how habitual, or automatic, the behaviour has become. Repeated initiation and repetition of a behaviour has been shown to result in an activity becoming more automatic. Thus, this study experimentally investigated the efficacy of the often recommended “Just Get Started” (JGS) tactic, which increases the likelihood of initiating a behaviour, and assessed whether it increased participants’ frequency and automaticity of flossing. Undergraduate students (n = 44) completed baseline surveys before being randomized into one of two groups: (1) a control group in which participants were only told to floss each day for four weeks, and (2) and a JGS group that was additionally given the recommendation to use the JGS tactic, that is, whenever they did not feel like flossing, to pick up the floss and floss one tooth before deciding whether or not to continue. Participants reported their frequency and automaticity of flossing after 2 and 4 weeks. Results showed that although both automaticity and flossing increased over time, there was no significant difference between the JGS and control group on these measures, suggesting that the JGS rule provided no extra benefit. Participants who made use of the JGS tactic, however, reported that the rule helped them initiate and continue flossing, which suggests that the JGS rule may be perceived as more useful than it actually is. Additional exploratory analyses revealed several differences in background experiences between flossers and non-flossers. Baseline flossing frequency also showed a small correlation with self-control, conscientiousness, and procrastination, and a strong correlation with automaticity. Limitations of the study include a small sample size and the over-reliance on self-report measures.
Presented on April 21, 2022 at Student Research Day at MacEwan University in Edmonton, Alberta.
Keywords: oral hygiene practices; flossing; undergraduates; self-reliance